GREEN SYNTHESIS OF SILVER NANOPARTICLES AND THEIR CATALYTIC APPLICATION FOR THE DEGRADATION OF ORGANIC POLLUTANTS - Skiba, M. I.; Pivovarov, О. А.; Vorobyova, V. I. (Вісник Черкаського державного технологічного університету, 2019)
A simple and rapid method of green synthesis of silver nanoparticles (AgNPs) was developed using aqueous extract of grape pomas (GP) obtained from by plasma-chemical extraction technique, and their catalitic potential was investigated. With this aim, the plasma-chemical obteained aqueous solutions of grape pomace and AgNO3 (0.25-6.0 mM) were mixed (1:1 v/v), and heated for 10 mim. The synthesized GP-AgNPs were characterized by UV-visible spectroscopy, AFM, DSL analyses. The synthesized AgNPs showed an intense surface plasmon resonance band at 405-420 nm. The AgNPs were in highly uniform shape (everage size 20 nm). The role of pH in the green synthesis of silver nanoparticles (AgNPs) is investigated. The presence of silver nanoparticles with sun light was proven very effective for degradation of organic dyes. The reaction kinetics was found to be pseudo first order with respect to the dye concentration. The outcomes of the current study confirmed that the synthesized AgNPs had an awesome guarantee for application in catalysis and wastewater treatmen.